Manajemen Rantai Pasok Halal di Indonesia: Analisis SWOT dan Implikasi Strategis: Halal Supply Chain Management in Indonesia: SWOT Analysis and Strategic Implications - Azwar, Azwar; Nasrullah bin Sapa (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2025)
This study aims to identify the key strengths, weaknesses, opportunities, threats, and strategic directions that influence the sustainability and effectiveness of Halal Supply Chain Management (HSCM) at the national level. Employing a mixed-methods approach with an exploratory sequential design, the research integrates qualitative and quantitative analyses through the SWOT framework and the Internal–External (IE) Matrix. The findings reveal that Indonesia possesses significant strategic potential to develop a globally competitive halal supply chain, supported by its large Muslim consumer base, robust regulatory framework, growing public awareness, and the rapid expansion of halal-oriented MSMEs. Nevertheless, several structural weaknesses persist, including limited halal logistics infrastructure, high certification costs, weak inter-agency coordination, and low halal literacy among business actors. Opportunities arise from the rapid expansion of the global halal economy, digital innovation (blockchain, IoT, big data), and increasing international demand for ethical and sustainable halal products. Meanwhile, the main challenges include competition with benchmark countries, varying international halal standards, and dependency on imported raw materials. The IE Matrix positions Indonesia in the high–high quadrant, indicating a growth strategy through vertical integration—strengthening local production, standardization, digital traceability, and institutional synergy. Through this strategic approach, Indonesia has the potential to transform from the world’s largest halal consumer market into a leading producer and innovation hub in the global halal economy.